The prevalence of work‐related suicides varies by reporting source from the National Violent Death Reporting System. Issue 7 (16th April 2021) - Peek‐Asa, Corinne; Zhang, Ling; Hamann, Cara; Davis, Jonathon; Casteel, Carri
Abstract: Introduction: Both suicides overall and work‐related suicides are increasing in the United States, and efforts to reduce suicide risk will require an understanding of the frequency and role of work in suicides. This study examines the incidence of occupational suicides using the National Violent Death Reporting System (NVDRS), which identified the role of work in suicides using the traditional death certificate as well as from death investigations. Methods: NVDRS suicides among those aged 16 through 65 from 2013 through 2017 were examined to determine if the death certificate identified the death as work‐related, if the death investigation identified a job problem as a suicide circumstance, and if the death investigation indicated that the job problem was a crisis at the time of the suicide. Results: Overall, 1.13% of death certificates identified the suicides as work‐related, 2.34% of suicides included a job crisis, and 11.2% a job problem, and proportions did not vary over the years of the study. Overlap between the death certificate and death investigation was very low, with only 0.21% of suicides identified as related to work by both sources. Identification of work‐relatedness varied by source for demographic characteristics, mechanism of suicide, and occupation. For example, the death certificate identified 2.1% of suicides among those working in protective services as work‐related, but death investigations identified 15.2% as having a job problem. Conclusion: Work‐related factors may be associated with a far higher proportion of suicides than previously documented.